A re-examination of the petroglyphs of Qatar - Pelling, Robyn; Cuttler, Richard; al-Naimi, Faisal Abdulla; Reis, Antonio Oliveira; Delaney, Liam (Proceedings of the Seminar for Arabian Studies, 2015)
Over the past sixty years petroglyphs found across the jebels of Qatar have been subject to significant discussion and debate. Since the middle of the last century, research has isolated over forty sites including the extensive al-Jassasiya, and other sites including al-Ghariya, Baia'a, Fraina, Fuwairit, and central Doha. Research by the Danish Archaeological Expedition (Glob 1957), and later by Hans Kapel (1983) produced an extensive catalogue of the al-Jassasiya site. Less exhaustive work has encompassed Umm al-Tuwaim, Fuwairit, Bala'a, and Fraiha. Specific images, such as boats, indicate a post-tenth-to thirteenth-century date (Facey 1987), while pottery has been used to suggest a date as late as the seventeenth to nineteenth centuries (de Cardi 1978). Scientific dating corroborates this with a mean age of 300 BP (Hassiba et al. 2012). Nonetheless, the age and provenance of the petroglyphs remains enigmatic. This paper aims to re-examine the existing data set and enmesh this corpus of knowledge with more recent work, which has been undertaken by Qatar Museums and the University of Birmingham's QNHER project. This latest work has included excavation and various survey techniques, including kite photography and GIS mapping and its aim was to provide fresh comment on the time frame during which the petroglyphs may have been created and who created them, as well as placing them within their archaeological context.